Gamma-ray spectrometry and magnetometry of the alkaline rock area in Ampipal-Bhulbhule, Nepal Lesser Himalaya - Gautam, P.; Sharma, M. P.; Dhakal, Subodh (Journal of Nepal Geological Society, 1998)
Gamma-ray spectrometric and magnetometric survey conducted in the Ampipal-Bhulbhule area characterised by the distribution of syenitic gneisses hosted by the metasediments of the Kuncha Formation revealed that such a geophysical complex is effective in mapping the contact zones of syenitic bodies with the host rocks. Altogether 84 sites within the syenitic bodies and 32 sites in the host rocks were probed by the spectrometer for responses in U, Th and 40K., and total counts windows. The syenites always give readings distinctly higher than the host rocks. Within the main syenitic body, the maximum radiometric response is obtained at the central part. Several sites within the syenitic gneisses yield anomalies in equivalent Uranium content (eUmax = 303.5 ppm) and Thorium content (eTHmax=213.6 ppm) and also in K-channel counts. Across the zone of contact between the syenites and the host metasandstones, both the radiometric counts (especially K-counts) and the magnetic effect vary significantly. Prominent magnetic anomaly has been detected at Bhulbhule Khar and it is interpreted to be the effect of either a thick layer of basic or ultrabasic rock enclosed within the nepheline syenite, or an economic Fe-mineralisation residing in magnetite. Thus, magnetic method also is clearly effective for mapping the subsurface distribution of dyke rocks and also Fe-mineralised areas.